PENGARUH EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN DI MORRISSEY HOTEL JAKARTA - Nurhaliza, Cornelia Putri; Afriasih, Maria Ulfah Catur; Dwilanisusantya, Carissa (Jurnal Perhotelan dan Pariwisata, 2024)
This study aims to examine the influence of employee engagement on employee performance at Morrissey Hotel Jakarta. A quantitative approach was employed using descriptive analysis methods. The study involved 62 respondents, consisting of both permanent and contract employees. Descriptive analysis revealed that the level of employee engagement was classified as very high, with the vigor dimension being the most dominant. However, the results of the simple linear regression analysis indicated that employee engagement did not have a significant effect on employee performance, as shown by a significance value of 0.054 (p > 0.05). These findings suggest that although employee engagement is high, it is not sufficient to enhance performance without support from other external factors. Therefore, the null hypothesis (H₀) is accepted, and the alternative hypothesis (H₁) is rejected. Keywords: Employee Engagement, Employee Performance, Simple Linear Regression, Human Resources, Morrissey Hotel Jakarta